Research on the development path of Chengdu as a low-carbon city under the dual constraints of carbon emission and economic growth - Yu, Ji; Yu, Lu; Luo, Yunan; Zhang, Peiwen (Frontiers in Environmental Science, 2024)
As the proportion of carbon emissions from urban areas rises, cities like Chengdu have become critical frontiers for emission reduction in China. Consequently, constructing low-carbon cities has emerged as the primary strategy for mitigating carbon emissions. According to the LMDI additive decomposition analysis, Chengdu’s carbon emissions increased by 4,397,700 tons during the 13th Five-Year Plan, primarily due to economic expansion, which alone accounted for an increase of 8,078,200 tons. Meanwhile, shifts in industrial structure and reductions in energy intensity contributed to declines of 657,700 tons and 3,016,500 tons, respectively, while changes in energy structure resulted in a marginal decrease of 640 tons. The LMDI multiplicative decomposition indicates a 10.3% growth in carbon emissions, with economic size amplifying emissions by 1.197 times, while enhanced energy intensity mitigated growth, reducing emissions to 0.935 times 2016 levels. Adjustments in industrial and energy structures exerted minimal impact on emission reductions. By developing a decomposition model for carbon emission influencing factors across various industries, this study identifies challenges to economic growth within the context of carbon reduction constraints and proposes pathways for low-carbon city development, including industrial restructuring, urban optimization, green building initiatives, and comprehensive transportation systems, thereby offering valuable insights for national low-carbon city initiatives.